JALALUDDIN RUMI: FILSAFAT CINTA DAN RELEVANSINYA TERHADAP PENDIDIKAN MULTIKULTURAL - Labib Mustofa; Akhmad Nurul Kawakib (UIN Raden Mas Said Surakarta, 2025)
This study examines the philosophy of love of Jalaluddin Rumi and its relevance to the education of diversity in Indonesia using a quasi-qualitative approach through literature review. The study interprets Rumi's concept of universal love, which transcends boundaries of identity such as religion, ethnicity, and culture, offering universal values such as compassion, respect for differences, and solidarity. These values are highly relevant in building diversity education that not only teaches tolerance but also strengthens social harmony amidst Indonesia's diversity. The results of the study show that integrating Rumi's principles of universal love into education can create an inclusive society that values diversity and contribute to the development of educational strategies based on Sufi values that enrich both the theory and practice of modern education in Indonesia.